KESIAPAN BERWIRAUSAHA PADA SISWA SMK NEGERI 1 MANDAU, KECAMATAN BATHIN SHOLAPAN, KABUPATEN BENGKALIS - Murni, Richy Restia; Ayub, Daeng; Jais, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine and analyze the level of entrepreneurial readiness among students of SMK Negeri 1 Mandau, Bathin Sholapan District, Bengkalis Regency. The background of the study was driven by government efforts to address poverty through vocational education. SMKs are generally tasked with preparing students for work or entrepreneurship. However, a phenomenon was found at SMK Negeri 1 Mandau that not all students have optimal readiness, characterized by a lack of self-confidence, limited capital, and minimal entrepreneurial experience. The entrepreneurial readiness variable is measured based on four indicators: self-confidence, courage to take risks, future-oriented, and creative and innovative. This study used a descriptive research type with a total of 82 students as respondents. The results showed that the average entrepreneurial readiness of SMK Negeri 1 Mandau students was 3.65, which is in the fairly high category interpretation. Specifically, the Light Vehicle Engineering (TKR) department had the highest average score of 4.13, while the Building Modeling & Information Design (DPIB) department had the lowest average score of 3.22. Overall, these findings indicate that the entrepreneurial readiness of students at SMK Negeri 1 Mandau is good and needs further improvement.